Analisis Daya Dukung Tanah Dan Bahan Pondasi Tiang Pancang Pada Pembangunan Jembatan Kab. Jombang - Ruslan Hidayat; Saiful Arfaah (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2019)
One of the most important factors in the structure of the pile foundation in the construction of the bridge is the carrying capacity of the soil so as not to collapse. Construction of a bridge in the village of Klitik in Jombang Regency to be built due to heavy traffic volume. The foundation plan to be used is a pile foundation with a diameter of 50 cm, the problem is what is the value of carrying capacity of soil and material. The equipment used is the Dutch Cone Penetrometer with a capacity of 2.50 tons with an Adhesion Jacket Cone. The detailed specifications of this sondir are as follows: Area conus 10 cm², piston area 10 cm², coat area 100 cm², as for the results obtained The carrying capacity of the soil is 60.00 tons for a diameter of 30 cm, 81,667 tons for a diameter of 35 cm, 106,667 tons for a diameter of 40 cm, 150,000 tons for a diameter of 50 cm for material strength of 54,00 tons for a diameter of 30 cm, 73,500 tons for a diameter of 35 cm, 96,00 tons for a diameter of 40 cm, 166,666 tons for a diameter of 50 cm